Laki-laki dan Kesetaraan Gender Pada Organisasi Solidaritas Perempuan Komunitas Anging Mammiri Sulawesi Selatan; Perspektif Hukum Islam - Muh Faizal P; Muhammad Sabir (Universitas Islam Negeri Alauddin Makassar, 2021)
The main problems in this research are: (1). What are the views of feminist men in the Women's Solidarity Organization for the Anging Mamiri Community on the issue of gender equality? (2). What are the forms of the women's feminist movement in the Anging Mammiri Community Women's Solidarity Organization on the issue of gender equality? The objectives of this study are (1). Knowing the mindset and point of view of men and women in Makassar. (2). Describe the activities and roles of feminist men in Makassar in gender problems in the life of the people of Makassar.This type of research is descriptive qualitative research with the research approach used is the Normative Sociology Approach and Historical Approach. The data sources of this research are primary data sources and secondary data sources. Furthermore, the data method used is the method of observation, interviews and documentation. Data processing and analysis techniques are processed in three stages, namely: data reduction, data presentation, and leveraging / drawing conclusions. The results of this study are: Men who have a feminist perspective view that the issue of gender equality is not only a problem involving women. More than that, this issue of equality in the global community because in practice it needs support and support from men because equality of speaking between relations between two sexes is different. The issue of gender equality exists because of a culture of male domination which is commonly referred to as a patriarchal culture. The gender equality movement carried out by feminist men in the Solidaritas Perempuan Anging Mammiri Community, South Sulawesi, implements programs within the organization. They also conduct regular reviews on gender equality issues published in Makassar so that they can take a little role for gender equality. They also began to apply equality in their own family roles. Thus they hope that this knowledge of gender equality can be widely practiced and initiated by members of their own families